Development of Problem-Solving-Based Science Teaching Materials to Improve Students Critical and Logical Thinking Skills - Sari, Sasmita; Sutarto, Joko; Lisdiana, Lisdiana (Universitas Negeri Semarang, 2021)
This research innovation is developing problem-solving-based science teaching materials that can help students solve problems in daily life and science and teaching materials can be tested for feasibility. This research is an important step in providing innovation in the development of science teaching materials and forming changes in the form an increase in students critical thingking and logical thingking skills. This research aims to develop problem-solving-based science teaching materials to improve the critical thinking and logical thinking skills of the learners. This Research & Development adopted Sugiyono’s model. The research design used was one groups pretest-posttest design with the member of subject were 58 students. The data collection techniques were interview, test, and questionnaire. The results of the interview show that there is a need for innovation in the development of science teaching materials. The results based on tes show that the problem-solving-based science teaching materials influenced the critical thinking and logical thinking skill improvements with the classical accomplishment 89%. The N-Gain score is 0.70, categorized high. The results based questinnaire show the teachers’ responses were 100% considered the material was very excellent. The results of the learners’ responses showed a percentage of 96.75% considered the material was very excellent. The content reliability, validity, display, and graph obtained a percentage of 86.54%, categorized as very reliable. Thus, the problem-solving-based teaching material was reliable for the learners to solve the lesson related to daily life. It could also improve the critical thinking and logical thinking skills of the learners.